Structure and function of the canine ventricular myocardium (Canis lupus familiaris): Ventricular myocardial band - De Lavalle, Rodrigo; Rendón, luis (Spei Domus, 2015)
Introduction: currently, there are new diagnostic tools and therapies for heart disease, but with no serious scientific consensus on the questions about the normal structure and function of the heart. Helical ventricular myocardial band of Torrent-Guasp is the revolutionary new concept in understanding global, three-dimensional, functional architecture of the ventricular myocardium. This concept defines the architecture and net forces developed within the ventricular mass. Materials and methods: 36 hearts of dogs of various weights, breeds and sexes were used to demonstrate the existence of a ventricular myocardial band in the canine myocardium by manual dissection. Results: the dissection performed showed a strong trend towards a continuous helical structure with a longitudinal arrangement of ventricular myocardial fibers, forming a single functional muscular band that begins at the height of the pulmonary artery and ends at the level of the aorta. Different segments of the band were identified: right (presence percentage 100 %) and left (100 %) with respect to parts of the basal loop, and descendant (100 %) and ascendant (100 %) in the dissection of the apical loop. Conclusions: the presence of the ventricular myocardial band in the canine myocardium (Canis lupus familiaris) was demonstrated and their structures identified. This is a new concept in the anatomy of the canine ventricular myocardium, where the complex network of the double helicoid is macroscopically evidenced. According to the theory of Torrent-Guasp, the canine myocardium would have the following contraction sequence: contraction of the basal loop, contraction of the descendant and ascendant segments of the apical loops, and ventricular ejection and suction.